Editorial: Trafficking in Minors: Confronting complex realities, structural inequalities, and agency - Oude Breuil, Brenda; Gerasimov, Borislav (Anti-Trafficking Review, 2021)
This Editorial introduces a Special Issue of the journal Anti-Trafficking Review of the topic of ‘Trafficking in Minors’. It argues that the urgency of the phenomena of child trafficking and related issues, such as child labour and child sexual exploitation, and the emotional responses they provoke, have often led to superficial and knee-jerk reactions that obscure the root causes of the problems and deflect attention and resources away from grounded, sustainable solutions. It presents a brief overview of the articles contained in the Special Issue and concludes that policy responses and practical interventions to address trafficking in minors need to have the best interest of the child in mind and address the underlying socio-economic and political root causes.